2017
DOI: 10.1152/ajplung.00247.2017
|View full text |Cite
|
Sign up to set email alerts
|

Alternative pre-mRNA splicing of Toll-like receptor signaling components in peripheral blood mononuclear cells from patients with ARDS

Abstract: A key physiological feature of acute respiratory distress syndrome (ARDS) is inflammation. Toll-like receptor (TLR) signaling is required to combat the infection that underlies many ARDS cases but also contributes to pathological inflammation. Several TLR signaling pathway genes encoding positive effectors of inflammation also produce alternatively spliced mRNAs encoding negative regulators of inflammation. An imbalance between these isoforms could contribute to pathological inflammation and disease severity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 83 publications
0
15
0
Order By: Relevance
“…Alternative splicing within the immune system can affect the type and magnitude of the inflammatory response, such as the production of a soluble form of TLR4 that is expressed upon LPS, which leads to inhibition of TNFα and NFκB serving as a negative feedback mechanism (19,20). Additionally, this mechanism has been characterized within signaling molecules (21,22), including TBK1 (23) and MyD88 (24), that produce the alternative RNA splice forms, TBK1s and MyD88s respectively, which function to limit the extent of the proinflammatory response. Alternative splicing can also result in the production of inflammatory signaling molecules, such as TRIF (25) and the proteins in the NFκB family (9) with altered activity or stability.…”
Section: Introductionmentioning
confidence: 99%
“…Alternative splicing within the immune system can affect the type and magnitude of the inflammatory response, such as the production of a soluble form of TLR4 that is expressed upon LPS, which leads to inhibition of TNFα and NFκB serving as a negative feedback mechanism (19,20). Additionally, this mechanism has been characterized within signaling molecules (21,22), including TBK1 (23) and MyD88 (24), that produce the alternative RNA splice forms, TBK1s and MyD88s respectively, which function to limit the extent of the proinflammatory response. Alternative splicing can also result in the production of inflammatory signaling molecules, such as TRIF (25) and the proteins in the NFκB family (9) with altered activity or stability.…”
Section: Introductionmentioning
confidence: 99%
“…For example, alternative pre-mRNA splicing can result in production of inflammatory signaling molecules with altered activity or stability (Cadalbert et al 2010;Han et al 2010;Phan et al 2006;Wells et al 2006). Additionally, some genes that encode positive effectors of inflammatory signaling can also produce alternate pre-mRNA splice forms that encode negative regulators of signaling (Blumhagen et al 2017;De Arras and Alper 2013;Deng et al 2008;Gray et al 2010;Hardy and O'Neill 2004;Iwami et al 2000;Janssens et al 2002;Koop et al 2011;Palsson-McDermott et al 2009;Rao et al 2005;Rosenstiel et al 2006), thus mediating a negative feedback loop to limit the extent of the inflammatory response. In a similar fashion, alternative pre-mRNA splicing has been shown to alter cellular metabolism (Clower et al 2010;Yang and Lu 2013;Satoh et al 2015).…”
mentioning
confidence: 99%
“…Several studies have reported an association of MyD88 isoform levels with inflammatory disease. MyD88-L but not MyD88-S is increased in PBMCs from patients with two different inflammatory lung diseases (acute respiratory distress syndrome and interstitial lung disease with an acute exacerbation) (11). The increase in MyD88-L without a corresponding alteration in MyD88-S could contribute to the inflammatory milieu in these patients.…”
Section: Discussionmentioning
confidence: 89%
“…Mouse studies were approved by the National Jewish Health Animal Care and Use Committee (IACUC). [8][9][10][11][12] week old mice of both sexes were obtained from the Jackson Laboratories (Bar Harbor, ME). These mice included C57BL/6J (stock #000664), TLR4 knockout mice (stock #029015), and TRIF knockout mice (stock # 005037).…”
Section: Mouse Studiesmentioning
confidence: 99%
See 1 more Smart Citation